Compared to Wildfire, Management Practices Reduced Old-Growth Forest Diversity and Functionality in Primary Boreal Landscapes of Eastern Canada - Martin, Maxence; Grondin, Pierre; Lambert, Marie-Claude; Bergeron, Yves; Morin, Hubert (Frontiers in Forests and Global Change, 2021)
Large primary forest residuals can still be found in boreal landscapes. Their areas are however shrinking rapidly due to anthropogenic activities, in particular industrial-scale forestry. The impacts of logging activities on primary boreal forests may also strongly differ from those of wildfires, the dominant stand-replacing natural disturbance in these forests. Since industrial-scale forestry is driven by economic motives, there is a risk that stands of higher economic value will be primarily harvested, thus threatening habitats, and functions related to these forests. Hence, the objective of this study was to identify the main attributes differentiating burned and logged stands prior to disturbance in boreal forests. The study territory lies in the coniferous and closed-canopy boreal forest in Québec, Canada, where industrial-scale logging and wildfire are the two main stand-replacing disturbances. Based on Québec government inventories of primary forests, we identified 427 transects containing about 5.5 circular field plots/transect that were burned or logged shortly after being surveyed, between 1985 and 2016. Comparative analysis of the main structural and environmental attributes of these transects highlighted the strong divergence in the impact of fire and harvesting on primary boreal forests. Overall, logging activities mainly harvested forests with the highest economic value, while most burned stands were low to moderately productive or recently disturbed. These results raise concerns about the resistance and resilience of remnant primary forests within managed areas, particularly in a context of disturbance amplification due to climate change. Moreover, the majority of the stands studied were old-growth forests, characterized by a high ecological value but also highly threatened by anthropogenic disturbances. A loss in the diversity and functionality of primary forests, and particularly the old-growth forests, therefore adds to the current issues related to these ecosystems. Since 2013, the study area is under ecosystem-based management, which implies that there have been marked changes in forestry practices. Complementary research will be necessary to assess the capacity of ecosystem-based management to address the challenges identified in our study.